2019
DOI: 10.1128/jcm.01231-18
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Implementation of a Diagnostic Algorithm for DNA Detection of Bordetella pertussis, B. parapertussis, and B. holmesii in a Pediatric Referral Hospital in Barcelona, Spain

Abstract: This study aimed to validate a comprehensive diagnostic protocol based on real-time PCR for the rapid detection and identification of Bordetella pertussis, Bordetella parapertussis, and Bordetella holmesii, as well as its implementation in the diagnostic routine of a reference children’s hospital. The new algorithm included a triplex quantitative PCR (qPCR) targeting IS481 gene (in B. pertussis, B. holmesii, and some Bordetella bronchiseptica strains), pIS1001 (B. parapertussis-specific) and rnase P as the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…It represents a crucial strategy for parasite load determination in clinical samples, and allows the number of parasites to be normalized by the DNA quantity present in the sample [15]. For human patients, the RNAse P is a commonly used target as an internal control of reaction [56][57][58][59][60][61][62]. In Leishmania however, there are no studies, except the present one, describing the use of an internal control to quantify parasite load from human patient's samples.…”
Section: Discussionmentioning
confidence: 99%
“…It represents a crucial strategy for parasite load determination in clinical samples, and allows the number of parasites to be normalized by the DNA quantity present in the sample [15]. For human patients, the RNAse P is a commonly used target as an internal control of reaction [56][57][58][59][60][61][62]. In Leishmania however, there are no studies, except the present one, describing the use of an internal control to quantify parasite load from human patient's samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have found that B. holmesii infections are rare and mostly occur in older children and adults. Valero-Rello et al reported that B. holmesii was detected in only 0.9% (only in patients [ 4 years old) of patients suspected of pertussis [28]. Burgos-Rivera also reported a low positive rate of 0.66% [29].…”
Section: Discussionmentioning
confidence: 98%
“…Current understanding of the whooping-cough etiology has changed, since it is not restricted to infections exclusively caused by B. pertussis , but embraces also pertussis-like illnesses caused by B. holmesii and B. parapertussis . B. pertussis is still a primary causative agent of whooping-cough, with B. holmesii , emerging as the second, and followed by B. parapertussis [ 10 , 12 , 13 , 28 ]. The relation between B. pertussis and B. holmesii infections remains unknown, but cases of the co-infection have been reported recently.…”
Section: Discussionmentioning
confidence: 99%